Pecuária leiteira: estudo de caso de transição agroecológica na Agrovila V do Assentamento Pirituba II Itapeva (SP) - Canholi, Patricia Fracarolli (2009)
This article discusses the ongoing agroecological transition process of dairy cattle raising in Agrovillage V of Pirituba II settlement, for which educational and methodological references have been used, all of them compatible with a sustainable rural development. The small family farming settlement is located in the mid-south region of São Paulo state, between Itapeva and Itaberá and its main activities are dairy cattle raising and conventional grain crops (corn and beans) farming. The agroecological transition was set out in 2003, as a result of interactive actions between the settled ranchers and students of Timbó Agroecology Group. Through adaptation of zootechnical and agroecological criteria to Agrovillage V dairy cattle raising, this study aims to contribute to (i) increase in environmental quality, as well as in (ii) increase in pastures and cattle productivity and (iii) socialization of the agroecological experiences of both the settled family farmers and the local rural producers. As a hypothesis, it is expected that the agrosystems biological balance is gradually reestablished, followed by gradual reduction in production costs and increase in production rates. As preliminary results, it is possible to point out that the references in use in the agroecological transition are not only contributing to the understanding of ecological principles applied to dairy cattle raising, but also to the implementation of practices, such as: isolation of Permanent Conservation Areas (APP) bordering pastures, recovery of degraded pasture areas, adoption of phytotherapic drugs to prevent mastitis, and adoption of daily sanitary procedures.